Prevalence of Eight or More Antenatal Care Contacts: Findings From Multi-Country Nationally Representative Data - Michael Ekholuenetale MSc (SAGE Publishing, 2021)
Optimal antenatal care is an important service required by women and babies. To promote healthy motherhood and for positive pregnancy outcomes, World Health Organization recently recommended a minimum of 8 ANC contacts. We aim to explore the prevalence of 8 or more ANC contacts using multi-country data. Urban dwellers, mothers with secondary or higher education, women from high household wealth, early birth order, and older mothers at childbirth had higher prevalence of 8 or more ANC contacts respectively. The pooled prevalence of 8 or more ANC contacts was 13.0%. Jordan had the leading prevalence of 8 or more ANC contacts (74.0%), followed by Ghana (43.0%) and Albania (30.0%). On the other hand, Senegal, Uganda, and Zambia had very low prevalence of 8 or more ANC contacts. There was heterogeneity in the prevalence of 8 or more ANC contacts across countries. There was low prevalence of 8 or more ANC contacts.